Memoir of Hate Spin in 2017 Jakarta’s Gubernatorial Election; A Political Challenge of Identity against Democracy in Indonesia - Winarni, Leni; Agussalim, Dafri; Bagir, Zainal Abidin (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2019)
This research attempts to investigate an intermingled relationship of political interest and religious issues, particularly in the Jakarta's Gubernatorial Issues in 2017. Basuki Tjahaya Purnama or Ahok, one of the governor candidate and also the former governor was accused of blasphemy issues after his speech in the Pramuka Island becomes viral. Although this case ended with a court, which ruled that he was guilty and received a sentence of 2 years in prison, this has become an unforgettable fact of Indonesian democracy. The proposed inquiry is how far religious issues influence political tension for based non-religion countries such as Indonesia. By using approach of hate Spin, within the combination of hate speech (vilification or offense-giving) and indignation of the offense-taking framework, this paper focuses on the entanglements of a political campaign and religious issues in the election period. This issue is significant for the reason that the tension of religious and political issues put both democracy and multiculturalism in Indonesia. Indeed, there is still a good opportunity for maintaining diversity through producing tolerance view, and enforcing the law for the actor of hate speech and hate spin.